A construção da clínica nos encontros: dos sabores aos saberes - Pugliesi, Marizilda Ferreira (2009)
This work argues the attendance of the Infantile Psychosis in a Health Public Institution, which constitutes a model of global attendance of children and teenagers, with their relatives, summarized in principles of interdisciplinary and the joint with other services of the community. It is placed in a proposal of an extented clinic, implied with the affirmation of the life in its creative power. I intend to study the game of the relations established between mothers and children who present with a pathological defensive organization, which consists in the infantile psychosis. Meanwhile, it is in the space of the kitchen where they meet each other that, leaving of lived situations, and where they choose recipes and all the unfolding elapses from them. It is in a kitchen where the flavors are, where it constitutes the knowledge. We live intense and tense moments through tears, slaps, beans or lemon cake. An established programming does not exist previously. To each meeting it creates an event and a power to affect and to be affected. To capture the signals that emerge without explaining them or interpret them, but mapping its displacements, in a game of passages and becomes, makes possible that something of new occurs, searching exits for a possible existence